Deciding to Enrol in a Cancer Trial: A Systematic Review of Qualitative Studies - Viljoen B; Chambers SK; Dunn J; Ralph N; March S (Journal of Multidisciplinary Healthcare, 2020)
Bianca Viljoen,1– 3 Suzanne K Chambers,1,2,4– 7 Jeff Dunn,1,2,4,5 Nicholas Ralph,1,3– 5 Sonja March1,8 1Centre for Health Research, Institute for Resilient Regions, University of Southern Queensland, Springfield, Brisbane, Australia; 2Cancer Council Queensland, Brisbane, Australia; 3School of Nursing & Midwifery, University of Southern Queensland, Toowoomba, Australia; 4Faculty of Health, University of Technology Sydney, Sydney, Australia; 5Australian and New Zealand Urogenital and Prostate Cancer (ANZUP) Trials Group, Sydney, NSW, Australia; 6Prostate Cancer Foundation of Australia, Sydney, NSW, Australia; 7Exercise Medicine Research Institute, Edith Cowan University, Perth, WA, Australia; 8School of Psychology and Counselling, University of Southern Queensland, Springfield, Brisbane, AustraliaCorrespondence: Nicholas RalphInstitute for Resilient Regions, University of Southern Queensland, Springfield, Brisbane, QLD 4350, AustraliaEmail nicholas.ralph@usq.edu.auBackground: Clinical trials are essential for the advancement of cancer treatments; however, participation by patients is suboptimal. Currently, there is a lack of synthesized qualitative review evidence on the patient experience of trial entry from which to further develop decision support. The aim of this review is to synthesise literature reporting experiences of participants when deciding to enrol in a cancer clinical trial in order to inform practice.Methods: A systematic review and meta-synthesis of qualitative studies were conducted to describe the experiences of adult cancer patients who decided to enrol in a clinical trial of an anti-cancer treatment.Results: Forty studies met eligibility criteria for inclusion. Three themes were identified representing the overarching domains of experience when deciding to enrol in a cancer trial: 1) need for trial information; (2) trepidation towards participation; and (3) justifying the decision. The process of deciding to enrol in a clinical trial is one marked by uncertainty, emotional distress and driven by the search for a cure.Conclusion: Findings from this review show that decision support modelled by shared decision-making and the quality of a shared decision needs to be accompanied by tailored or personalised psychosocial and supportive care. Although the decision process bears similarities to theoretical processes outlined in decision-making frameworks, there are a lack of supportive interventions for cancer patients that are adapted to the clinical trial context. Theory-based interventions are urgently required to support the specific needs of patients deciding whether to participate in cancer trials.Keywords: advanced cancer, qualitative, guideline development, consolidated framework for implementation research